(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Higher education is currently trending more in the direction of management. Additionally, a growing number of students want to pursue degrees in management. B-Schools offering management education are supposed to be student-centred in accordance with the times. The study’s main focus is on how the students at the aforementioned institutions must be handled. Four elements have been taken into consideration in this context: students as partners, customers, products, and stakeholders. The preferences and views of the students have been examined in light of this. First, the study shows that the preferences and perceptions of the students differ significantly. Second, stakeholders, partners, and customers should be viewed more like products than students.